On-line detection of fretting fatigue crack initiation by lock-in thermography. (April 2017) - Chhith, Saosometh; De Waele, Wim; De Baets, Patrick; Van Hecke, Tanja
Abstract: Lack of accurate methodologies to detect micro-cracks in fretting fatigue experiments is a barrier to better understand the physics of the crack initiation phenomenon. In this study, the feasibility of thermography for on-line detection of micro-cracks in a closed contact during fretting fatigue experiments is investigated. Temperature variations in four regions of interest at the specimen surface are recorded and processed on-line based on a lock-in methodology to extract the first harmonic temperature amplitude. Following running-in and stabilization stages, the initiation of cracks leads to a rise of the stabilized first harmonic temperature amplitude for the specific region of interest where cracks are located. After that, tests are stopped and samples are inspected for cracks by optical microscopy. Highlights: The temperature data can be grabbed and processed on-line with a Matlab script without storage issues. The standard lock-in or Fast Fourier transform algorithms allow to reduce the signal-to-noise ratio from 25 mK to 2 mK. The thermo-elastic temperature amplitude can be used as an indicator for on-line crack initiation. The methodology is expected to work for any fatigue tests if the crack location can be estimated in advance.